STUDI PENERAPAN STRATEGI SEGMENTASI PASAR, TARGET PASAR DAN PENEMPATAN POSISI GUNA PENINGKATAN JUMLAH KONSUMEN PADA HOTEL KARTIKA WIJAYA BATU - Eni Maryati, Wahyu (Department Industrial Engineering, University of Muhammadiyah Malang, 2001)
Market segmentationh ave purpose to devide plural customersi nlo the same marketsegmentationF. rom this segment,m arket sharet hat will be served dependingt o the segmentt hat givemaximum profit for Kartika Wijaya Hotel Batu.The methodu sedi n this researchis usingc lustera nalysisw ith SPSSp rograma s a help.T hesecondm ethodt hat be usedi s caracteristiacn alysism ethodo f customeres achs egmenut singc rossT absanalysisa nd the third methodu singp references tructurea nalysism ethodo f segmenut sing Thurstone'scase analysis.In customers egmentatioann alysisu singc lastera nalysisc an got 5 segments4.. of 5 balancesegmentfso rmedc ustomer'sp rofile caracterislice very segmenbt asedo n demografvi ariatesb, ehaviors,and advantagesA. nd from customer'sp references truclure concludet hat the prize that have beend ecidedby companyim portanat spect/s a tributeso f customer.